2021
DOI: 10.3390/ijms22094906
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated Bifidobacterium bifidum and Lactobacillus gasseri in Combination with Quercetin Inhibit Colorectal Cancer Development in ApcMin/+ Mice

Abstract: Recent studies have suggested that flavonoids such as quercetin and probiotics such as Bifidobacterium bifidum (Bf) and Lactobacillus gasseri (Lg) could play a relevant role in inhibiting colon cancer cell growth. Our study investigated the role of dietary supplementation with microencapsulated probiotics (Bf and Lg) along with quercetin in the development of mouse colorectal cancer (CRC). Methods: Adenomatous polyposis coli/multiple intestinal neoplasia (ApcMin/+) mice were fed a standard diet or the same die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…From the perspective of the tumor nodule number, quercetin has been observed to positively impact the prognosis of the tested rodents [ 139 , 162 , 163 , 164 ]. However, the molecular mechanism was not monitored in the reviewed studies ( Table 7 ).…”
Section: Quercetin Impacts Tumor Nodule Number In Crcmentioning
confidence: 99%
“…From the perspective of the tumor nodule number, quercetin has been observed to positively impact the prognosis of the tested rodents [ 139 , 162 , 163 , 164 ]. However, the molecular mechanism was not monitored in the reviewed studies ( Table 7 ).…”
Section: Quercetin Impacts Tumor Nodule Number In Crcmentioning
confidence: 99%
“…Moreover, the dietary supplementation decreased the number of ACF as compared to D group, as found in [37]. Finally, the inhibition of tumor formation due to dietary sphingomyelin has been attributed to a normalization of cell proliferation and rate of apoptosis, but not the induction of differentiation [12].…”
Section: Discussionmentioning
confidence: 84%
“…Although non-steroidal anti-inflammatory drugs are able to reduce the number of polyps in FAP, severe cardiovascular effects have been reported [20], pointing out the need to find alternative treatments without the risk of developing side effects. Experimental models recently suggested that dietary supplements (phytoestrogens, insoluble fibers, probiotics, quercetin, n-3 polyunsaturated fatty acids) might be useful to reduce intestinal carcinogenesis in rats mutated in the APC gene [21][22][23][24]. Recently, a small non-randomized study of three-month oral supplementation with phytoestrogens and indigestible insoluble fibers showed a reduction in the number and size of duodenal polyps in FAP individuals [25].…”
Section: Discussionmentioning
confidence: 99%